A comparative study on wear and friction characteristics of phenolic composite coatings filled with different morphologies ZnO. (4th March 2019) - Wu, Liangfei; Zhang, Zhaozhu; Yang, Mingming; Yuan, Junya; Men, Xuehu; Guo, Fang
Abstract : In this paper, different morphologies ZnO (disk‐like, rod‐like, and nanoparticles) were introduced into phenolic composite coatings to comparatively investigate the tribological properties. The structural and morphological characterization was conducted with Raman spectroscopy, X‐ray diffraction, and scanning electron microscopy. The tribological performances of composite coatings were evaluated using ring‐on‐block tester under dry condition at room temperature. Experimental results indicated that composite coatings filled with 1 wt% ZnO micro‐disks possessed the optimal tribological performances. It was attributed to the strong interfacial interaction between ZnO micro‐disks and phenolic matrix induced by their specific polar structure. Moreover, different loads and sliding speeds were employed to further evaluate the tribological performances of ZnO micro‐disks/phenolic composite coatings. The outcome revealed that ZnO micro‐disks were potential anti‐wear fillers under harsh condition.